Hepatitis B virus polymerase impairs interferon‐α–induced STA T activation through inhibition of importin‐α5 and protein kinase C‐δ123. Issue 2 (5th February 2013) - Chen, Jieliang; Wu, Min; Zhang, Xiaonan; Zhang, Wen; Zhang, Zhanqing; Chen, Lixiang; He, Jing; Zheng, Ye; Chen, Cuncun; Wang, Fan; Hu, Yunwen; Zhou, Xiaohui; et al.
Abstract Treatment with exogenous interferon (IFN)‐α is not effective in the majority of patients with chronic hepatitis B virus (HBV) infection. Recent evidence suggests that HBV has evolved strategies to block the nuclear translocation of signal transducer and activator of transcription (STAT) 1 to limit IFN‐α–induced cellular antiviral responses. However, it remains unclear whether STAT1 translocation is impaired in chronic hepatitis B patients and what mechanisms are involved. Here we report that the expression of HBV polymerase (Pol) in human hepatic cell lines inhibited induction of IFN‐stimulated genes and resulted in a weakened antiviral activity of IFN‐α. Ectopic expression of Pol suppressed IFN‐α–induced STAT1 serine 727 phosphorylation and STAT1/2 nuclear accumulation, whereas STAT1 tyrosine 701 phosphorylation, and STAT1‐STAT2 heterodimer formation were not affected. Further studies demonstrated that Pol interacted with the catalytic domain of protein kinase C‐δ (PKC‐δ) and perturbed PKC‐δ phosphorylation and its association with STAT1, which resulted in the suppression of STAT1 Ser727 phosphorylation. Moreover, Pol was found to interfere with nuclear transportation of STAT1/2 by competitively binding to the region of importin‐α5 required for STAT1/2 recruitment. Truncation analysis suggested that the terminal protein and RNase H domains of Pol were able to bind to PKC‐δ and importin‐α5, respectively, and were responsible for the inhibition of IFN‐α signaling. More importantly, the inhibition of STAT1 and PKC‐δ phosphorylation were confirmed in a hydrodynamic‐based HBV mouse model, and the blockage of IFN‐α–induced STAT1/2 nuclear translocation was observed in HBV‐infected cells from liver biopsies of chronic HBV patients. Conclusions: These results demonstrate a role for Pol in HBV‐mediated antagonization of IFN‐α signaling and provide a possible molecular mechanism by which HBV resists the IFN therapy and maintains its persistence. (HEPATOLOGY 2013;)